The impact of weight reduction therapy on blood pressure levels in Primary Care - Arantes, Daniel Victor (2006)
In the last decades the incidence and prevalence of overweight and obesity are increasing drastically over the world. It is estimated that in Brazil 32% of adults are overweight and 8% obese, totalizing 40% of adults over the weight levels recommended for a healthy life. The situation is even more critical in the low-income population with poor educational level, where the problem is advancing even faster. Obesity figures among the most important risk factors for cardio-vascular diseases and there is strong scientific evidence that even modest weight reduction leads to significant clinical benefits. Thus, offering treatment for overweight and obesity in primary care can evidently improve the health and quality of life of the population and reduce the final public health expenditures. The purpose of this study is to evaluate the applicability and impact of a weight reduction program on the blood pressure levels of a group of patients assisted in a public primary care program called ‘Estratégia de Saúde da Família’ (Family Health Strategy) and to propose ways for standardizing this program. A retrospective analytic study was conducted for comparing the clinical data of patients submitted to weight reduction therapy in a public primary care unit called ‘Unidade de Saúde da Família Bandeiras’ in Anápolis, State of Goiás, Brazil. Informed consent from the patients was obtained. Exclusion and inclusion criteria were applied to correct deviations, resulting in a homogeneous sample of 28 patients. Blood pressure and weight levels were obtained before and after the treatment. The arithmetic means of weight, height and blood pressure at the beginning of the treatment were compared with those obtained six months after the treatment was started. There was a mean reduction of 0,64mmHg in the systolic blood pressure (SBP) levels and of 0,84mmHg in the diastolic blood pressure (DBP) levels for each 1kg of weight loss. These data confirm those found in the literature, indicating for each weight loss of 1kg a reduction of 0,88 and 0,72mmHg in SBP and DBP respectively. Weight reduction of at least 10% provides significant clinical benefit, especially in patients with metabolic syndrome and/or cardiovascular disease. The diagnosis is simple and the treatment cost effective, especially if provided by means of a standardized program including educational group activities motivating the patients to change their life habits. Pharmacotherapy may be useful and secure in primary care if offered as adjunctive treatment. This study shows that a standardized primary care-based weight reduction program can be inexpensive and effective for promoting the clinical benefits well described in the scientific literature.